2018
DOI: 10.1186/s12917-018-1686-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of a conventional SPCE for FMD post-vaccination monitoring

Abstract: BackgroundFoot-and-mouth disease (FMD) can be controlled by either stamping out or vaccination, a choice which depends on both the economic importance of the livestock sector as well as the disease status. In FMD-free countries with vaccination, such as Korea, vaccination programs should guarantee prevention against transmission of FMD. Monitoring of vaccination programs is also essential for ensuring sufficient coverage that will limit the transmission of FMDV. There are several methods to screen FMD virus (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Among these tests, SPCE is widely used for primary screening to determine SP Abs in field samples due to the time and labor consumption of VNTs as well as the lack of antigen stability of LPBE. For the accurate diagnosis of FMD, SPCE for FMD is currently also needed to improve sensitivity and specificity [28]. Many efforts have been made to develop mAbs against SP Abs for FMDV type A [29][30][31], but it has been required to develop a FMDV type A SPCE with higher sensitivity and specificity until now.…”
Section: Discussionmentioning
confidence: 99%
“…Among these tests, SPCE is widely used for primary screening to determine SP Abs in field samples due to the time and labor consumption of VNTs as well as the lack of antigen stability of LPBE. For the accurate diagnosis of FMD, SPCE for FMD is currently also needed to improve sensitivity and specificity [28]. Many efforts have been made to develop mAbs against SP Abs for FMDV type A [29][30][31], but it has been required to develop a FMDV type A SPCE with higher sensitivity and specificity until now.…”
Section: Discussionmentioning
confidence: 99%
“…Solid-phase competition ELISA kits for detection of specific SPs of FMDV of different serotypes were commercially available. Nevertheless, one recent study reported that the sensitivity of the SPC-ELISA kit for specific detection of FMDV serotype O was lower, and it produced more false-positive results as compared to LPB-ELISA and VNT ( 78 ).…”
Section: Serological Methodsmentioning
confidence: 99%
“…The presence of serotype specific anti-SP antibodies in serum samples was tested by using the FMD SPC ELISA kits (IZSLER, Biotech Lab, Italy). Selected neutralizing anti-FMDV monoclonal antibodies were used in solid phase competitive ELISA, specific for FMDV serotype Asia 1, O, and A to measure antibodies against these serotypes (Kang et al, 2018). Optical density of the test wells compared to the control wells was read by a microplate photometer (Thermo, 590741) and interpreted as negative or positive based on the percentage inhibition (PI).…”
Section: Solid-phase Competitive Elisa (Spc Elisa)mentioning
confidence: 99%